2012
DOI: 10.3390/ijms131013605
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Tendon–Bone Healing for Anterior Cruciate Ligament (ACL) Reconstruction Using Bone Marrow-Derived Mesenchymal Stem Cells Infected with BMP-2

Abstract: At present, due to the growing attention focused on the issue of tendon–bone healing, we carried out an animal study of the use of genetic intervention combined with cell transplantation for the promotion of this process. Here, the efficacy of bone marrow stromal cells infected with bone morphogenetic protein-2 (BMP-2) on tendon–bone healing was determined. A eukaryotic expression vector containing the BMP-2 gene was constructed and bone marrow-derived mesenchymal stem cells (bMSCs) were infected with a lentiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 34 publications
1
60
0
Order By: Relevance
“…To the best of our knowledge, bone formation and tendon-to-bone healing are important factors in ACL reconstruction, and the healing of the tendon-to-bone interface is crucial to some orthopedic procedures and essential for the long-term survival of patients undergoing ACL reconstruction [27,28]. BMSCs are considered to be multipotent cells that can differentiate into mesenchymal-lineage cell types both in vivo and in vitro and have long been identified as promising molecules for engineered tissue repair and cell therapy [6,25]. Lim et al noted that MSCs promote better ACL reconstruction by biologically changing the normal healing process of the hamstring tendon grafts to their ambient bone tunnels, and the application of MSCs to the tendon grafts enhances graft osteointegration and healing through the formation of an intervening chondroid layer resembling the chondral enthesis of normal ACL insertions [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, bone formation and tendon-to-bone healing are important factors in ACL reconstruction, and the healing of the tendon-to-bone interface is crucial to some orthopedic procedures and essential for the long-term survival of patients undergoing ACL reconstruction [27,28]. BMSCs are considered to be multipotent cells that can differentiate into mesenchymal-lineage cell types both in vivo and in vitro and have long been identified as promising molecules for engineered tissue repair and cell therapy [6,25]. Lim et al noted that MSCs promote better ACL reconstruction by biologically changing the normal healing process of the hamstring tendon grafts to their ambient bone tunnels, and the application of MSCs to the tendon grafts enhances graft osteointegration and healing through the formation of an intervening chondroid layer resembling the chondral enthesis of normal ACL insertions [29].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately a quarter of patients have dissatisfactory long-term results, with clinical outcomes indicative of osteoarthritic changes in the knee joint [1]. Since the success and failure of surgery are largely dependent on the biological healing between the bone tunnel and graft, and the early connection of tendon-bone interface has been shown to be the weakest link [6], it is pivotal to investigate better strategies to improve the healing of tendon-to-bone interface.…”
Section: Introductionmentioning
confidence: 99%
“…BMP is the most useful growth factor with osteoinductive ability [32]. Among the known BMPs, BMP-2 has the most pronounced effect on promoting defect repair and in healing fractures [33]. bFGF, a potent angiogenic factor and bone regeneration factor, induces specialization of MSCs in vitro and bone repair in vivo [17].…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells genetically modified to overexpress the developmental gene membrane type 1-matrix metalloproteinase also augmented rotator cuff healing at 4 weeks as shown by the presence of more fibrocartilage at the insertion site and improved biomechanical strength. Dong et al [23] found that MSCs genetically modified to overexpress BMP-2 improved tendon-bone healing in anterior cruciate ligament reconstructions. Tian et al [25] reported that MSCs significantly elevated the levels of ultimate load to failure, stiffness and stress in the Achilles tendons of rats, the effects of which were enhanced by chemokine (C-X-C motif) ligand 13.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation was assessed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetra-zolium bromide (MTT) assays as described previously [23]. In brief, 72 h after infection, cells were trypsinized and resuspended in DMEM (1 × 10 6 cells/mL).…”
Section: Mtt Assaymentioning
confidence: 99%